Simulation of three‐dimensional elastoacoustic wave propagation based on a Discontinuous Galerkin spectral element method. (5th February 2020) - F. Antonietti, Paola; Bonaldi, Francesco; Mazzieri, Ilario
Summary: In this article, we present a numerical discretization of the coupled elastoacoustic wave propagation problem based on a discontinuous Galerkin spectral element approach in a three‐dimensional setting. The unknowns of the coupled problem are the displacement field and the velocity potential, in the elastic and the acoustic domains, respectively, thereby resulting in a symmetric formulation. After stating the main theoretical results, we assess the performance of the method by convergence tests carried out on both matching and nonmatching grids, and we simulate realistic scenarios where elastoacoustic coupling occurs. In particular, we consider the case of Scholte waves, the scattering of elastic waves by an underground acoustic cavity, and a problem of marine seismic exploration. Numerical simulations are carried out by means of the code SPEED, available at http://speed.mox.polimi.it .